History of anomalies in physical and mental health in agribusiness workers in people management (Research, Society and Development, 2022)
This research constitutes a history of the anomalies of physical and mental health, with situations that suggest mitigating actions of the problematic in the management of people of rural workers in the national agribusiness scenario. It aimed to approach the obstacles in the health management process as well as the possible solutions that rural organizations exercise in their human resources area. Of qualitative nature, it constitutes a literature review with journal articles published from 2017 to 2021 that address the facts inherent to the health of the rural man. The results point to a variety of events related to health management that can be mitigated with the use of strategies and models that already exist within rural organizations. It is concluded that the instrumentalization of measures for the health of rural workers can slow down the rural exodus and the shortage of labor in the countryside, which strengthens the worker's health policy in the rural environment.